Strategi Perancangan Dan Penerapan Konten Instagram @Helloskinhouse Untuk Meningkatkan Engagement - Sari, Nurmala; Nasrullah, Muchamad Fajri amirul (Politeknik Negeri Batam, 2025)
The growth of the beauty industry in Batam demands business owners, such as Hello Skin, implement effective digital marketing strategies, particularly through the Instagram social media platform. This study aims to design and implement a content marketing strategy for the Instagram account @helloskinhouse to enhance customer engagement. The development method used is design thinking, comprising five stages, empathize, define, ideate, prototype, and test. Data were collected through observations, interviews, and the distribution of questionnaires to 202 respondents, who are followers of @helloskinhouse. The results of the study indicate that the implementation of the content marketing strategy, which includes a variety of content types, persuasive copywriting, appealing visuals, the use of relevant hashtags, and optimal posting times, significantly increased audience interactions by 2,500%. The content marketing index reached 86.20%, and customer engagement achieved 87.22%, both of which are categorized as excellent. Simple linear regression and partial tests (t-tests) demonstrated that content marketing has a positive and significant effect on customer engagement (significance value < 0.05). Thus, a well-structured content marketing strategy has been proven effective in increasing audience engagement and building brand trust on the @helloskinhouse Instagram account amid the competitive beauty industry.